2014
DOI: 10.1080/1045988x.2013.859562
|View full text |Cite
|
Sign up to set email alerts
|

Dance and Special Education

Abstract: Arts activities have been included in the educational curriculum of public schools for a number of years. Most often, course offerings in the arts consist of visual art, vocal music, and instrumental music classes. Although not as common, dance has also been included in the educational curriculum. Research and anecdotal evidence suggest that participating in dance activities can lead to positive student outcomes for students with and without exceptionalities. Dance activities appear to provide an alternative w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
0
3
0
2
Order By: Relevance
“…A creative dance and movement program had been implemented in Head Start schools, and very positive effects of dance were observed on children's social skills (Lobo & Winsler, 2006). Researchers reported that dance increases pre-school children's social-emotional skills (Lorenzo Lasa, Ideishi, & Ideishi, 2007;Munsell, Bryant & Kimberly, 2015;Piermen, 2020) and communication skills (Pavlidou, Sofianidou, Lokosi & Kosmidou, 2018). Thom (2010) found that body and movement exercises in the pre-school curriculum positively affected children's social-emotional adjustments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A creative dance and movement program had been implemented in Head Start schools, and very positive effects of dance were observed on children's social skills (Lobo & Winsler, 2006). Researchers reported that dance increases pre-school children's social-emotional skills (Lorenzo Lasa, Ideishi, & Ideishi, 2007;Munsell, Bryant & Kimberly, 2015;Piermen, 2020) and communication skills (Pavlidou, Sofianidou, Lokosi & Kosmidou, 2018). Thom (2010) found that body and movement exercises in the pre-school curriculum positively affected children's social-emotional adjustments.…”
Section: Discussionmentioning
confidence: 99%
“…According to Munsell, Bryant, and Kimberly (2015), many structured programs have been developed to improve young children's social skills, but few have recognized the role of art in improving social skills. In fact, the role that dance and movement activities can play in the process has often been overlooked.…”
Section: Dance Education In Early Agesmentioning
confidence: 99%
“…Participating in dance activities offers an alternative way to complete students' education, with or without educational needs, by improving their physical condition and by influencing social, psychological and educational sectors (Munsell, Bryant & Kimberly, 2016;Reinders, Bryden & Fletcher, 2015). Cultural associations play an important role in dance, recreational activities, organizing dance activities and performances throughout Greece and abroad (Serbezis, 1995).…”
mentioning
confidence: 99%
“…Οι χορευτικές δραστηριότητες προσφέρουν έναν εναλλακτικό τρόπο, για να συμπληρωθεί η εκπαίδευση μαθητών με ή χωρίς εκπαιδευτικές ανάγκες, βελτιώνοντας την φυσική κατάσταση, και επιδρώντας σε κοινωνικο-ψυχολογικούς και ακαδημαϊκούς τομείς (Munsell, Bryant & Kimberly, 2016;Reinders, Bryden & Fletcher, 2015 ).…”
Section: χορός κοινωνικές δεξιότητες κοινωνική συμπεριφοράunclassified
“…Τα αποτελέσματα συμφωνούν με μελέτες, οι οποίες αναφέρουν ότι η συμμετοχή σε χορευτικές δραστηριότητες, ως δραστηριότητες αναψυχής, σχετίζεται με χαμηλότερα επίπεδα παραβατικής συμπεριφοράς και υψηλότερα επίπεδα κοινωνικής συμπεριφοράς (Acquaviva, 2012;Mahoney & Stattin, 2000). Ακόμη, ότι οι χορευτικές δραστηριότητες προσφέρουν έναν εναλλακτικό τρόπο, για να συμπληρωθεί η εκπαίδευση μαθητών με ή χωρίς εκπαιδευτικές ανάγκες, βελτιώνοντας την φυσική κατάσταση, και επιδρώντας σε κοινωνικο-ψυχολογικούς και ακαδημαϊκούς τομείς επίδοσης (Munsell, Bryant & Kimberly, 2016;Reinders, Bryden & Fletcher, 2015).…”
Section: συζήτηση για την συμβολή των εκπαιδευτικών προγραμμάτων παραδοσιακού χορού στις κοινωνικές δεξιότητες των εφήβων σύμφωνα με τις unclassified